2010
DOI: 10.1095/biolreprod.109.080564
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced Segregation of Donor Mitochondria Introduced by Bovine Ooplasmic Transfer to the Female Germ-Line1

Abstract: Ooplasmic transfer (OT) has been used in basic mouse research for studying the segregation of mtDNA, as well as in human assisted reproduction for improving embryo development in cases of persistent developmental failure. Using cattle as a large-animal model, we demonstrate that the moderate amount of mitochondria introduced by OT is transmitted to the offspring's oocytes; e.g., modifies the germ line. The donor mtDNA was detectable in 25% and 65% of oocytes collected from two females. Its high variation in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 66 publications
3
48
0
4
Order By: Relevance
“…In addition, microinjection of mitochondria obtained from the same breed improved embryo quality during preimplantation development. There is a segregation of donor mitochondria by the oocyte after cytoplasmic transfer (Ferreira et al, 2010) supporting the hypothesis that mitochondrial homoplasmy is optimal.…”
Section: Mitochondriasupporting
confidence: 60%
“…In addition, microinjection of mitochondria obtained from the same breed improved embryo quality during preimplantation development. There is a segregation of donor mitochondria by the oocyte after cytoplasmic transfer (Ferreira et al, 2010) supporting the hypothesis that mitochondrial homoplasmy is optimal.…”
Section: Mitochondriasupporting
confidence: 60%
“…Moreover, detailed screening for buffalo mtDNA in offspring using a real-time protocol able to detect as little as 0.01% of buffalo mtDNA, was unsuccessful in identifying any vestige of buffalo mtDNA in somatic (blood, skin, muscle, and liver) and germline (oocytes) tissues of both calves born from XOT. Ferreira et al (2010), using a similar approach to that described in the present work, have performed ooplasmic transfer between B. indicus and B. taurus cows and found …”
Section: Resultsmentioning
confidence: 78%
“…Mitochondrial DNA analysis of children born following the procedure demonstrated that the contribution of donor mtDNA is small [92], but, in some cases, the proportion of donor mtDNA far exceeded the expected 10–15% [93], based on the volume of cytoplasm derived from the donor. While genetic drift might occasionally underlie such a change, experiments on bovine zygotes suggest that mitochondrial replacement can be consistently improved by centrifugation and removal of the recipient mtDNA without apparent effects on development [94], [95]. Centrifugation causes mitochondria to concentrate in one of the zygote's poles [94], [95], allowing removal of mitochondrion-enriched cytoplasm by micromanipulation.…”
Section: Is Nuclear Transfer the Way Forward?mentioning
confidence: 99%